Breeding site fidelity is lower in polygamous shorebirds and male-biased in monogamous species. (1st April 2022) - Kwon, Eunbi; Valcu, Mihai; Cragnolini, Margherita; Bulla, Martin; Lyon, Bruce; Kempenaers, Bart
Abstract: Sex-bias in breeding dispersal is considered the norm in many taxa, and the magnitude and direction of such sex-bias is expected to correlate with the social mating system. We used local return rates in shorebirds as an index of breeding site fidelity, and hence as an estimate of the propensity for breeding dispersal, and tested whether variation in site fidelity and in sex-bias in site fidelity relates to the mating system. Among 111 populations of 49 species, annual return rates to a breeding site varied between 0% and 100%. After controlling for body size (linked to survival) and other confounding factors, monogamous species showed higher breeding site fidelity compared with polyandrous and polygynous species. Overall, there was a strong male bias in return rates, but the sex-bias in return rate was independent of the mating system and did not covary with the extent of sexual size dimorphism. Our results bolster earlier findings that the sex-biased dispersal is weakly linked to the mating system in birds. Instead, our results show that return rates are strongly correlated with the mating system in shorebirds regardless of sex. This suggests that breeding site fidelity may be linked to mate fidelity, which is only important in the monogamous, biparentally incubating species, or that the same drivers influence both the mating system and site fidelity. The strong connection between site fidelity and the mating system suggests that variation in site fidelity may have played a role in the coevolution of the mating system, parental care, and migration strategies. Abstract : Birds may return to the same breeding site to reunite with their old partner. For migratory bird species, whether to return to the same site as last year to breed or disperse to a new site depends on their mating system. Among 49 species of shorebirds from around the globe, species that form an exclusive breeding pair returned to the previous breeding site more than species where one sex mates with multiple partners.